مفهوم الأُمَّة وأوصافها في القرآن الكريم - توفيق البدري (International Institute of Islamic Thought, 2018)
يهدف البحث إلى بيان مفهوم الأُمَّة عامَّةً، واستكناه حقيقة الأُمَّة الوارثة للملَّة الإبراهيمية خاصَّةً في القرآن الكريم، مع الإشارة إلى دلالة هذا المفهوم الأصلية في اللسان العربي، وما اكتسبه في الاستعمال القرآني. وقد تَبيَّن بعد استقراء اللفظ المدروس أنَّه مصطلح قرآني مُركَّب من حقائق ومقوِّمات، وأنَّه لا يُمكِن إدراك ماهيته في كلِّيتها إلا باستحضار العناصر التي تُشكِّل أركانه. وبهذا الاعتبار، فإنَّ أُمَّة الإسلام تشمل أتباع النبي الخاتم r الذين أسلموا وجوههم لله رب العالمين، فاستحقوا أنْ يكونوا بمقتضى الجَعْلِ الإلهي "خير أُمَّة"، و"أُمَّة مسلمة"، و"أُمَّة الوسطية"، و"أُمَّة واحدة"، و"شهداء على الناس". وهذه الخصائص هي التي تُكوِّن بمجموعها حقيقة الأُمَّة في القرآن الكريم. The purpose of this study is to demonstrate the concept of Ummah, in general and the essense of the Ummah who has inherited the faith of Prophet Ibrahim as explained in the Holy Quran, with reference to the original meaning of ummah in the Arabic tongue, and it has acquired in the Quranic usage. The scrutiny of the concept has revealed that it is a Qur'anic term composed of certain facts and has certain pillars, and it is difficult to get into its essense without recalling these facts and pillars. With this consideration, the Ummah of Islam includes the followers of Prophet Muhammad, peace be upon him, who turned their faces to Allah the Lord of the Worlds. Upon this kind of faith those followers deserve to have the Devine decree to be considered the "best ummah", the "Muslim ummah", the moderate ummah", the "one ummah" and the ummah whose members are "witnesses to mankind" These characteristics all together constitute the reality of the ummah in the Holy Quran.